2012
DOI: 10.1029/2012sw000826
|View full text |Cite
|
Sign up to set email alerts
|

GNSS measurement of EUV photons flux rate during strong and mid solar flares

Abstract: 1] A new GNSS Solar Flare Activity Indicator (GSFLAI) is presented, given by the gradient of the ionospheric Vertical Total Electron Content (VTEC) rate, in terms of the solar-zenithal angle, measured from a global network of dual-frequency GPS receivers. It is highly correlated with the Extreme Ultraviolet (EUV) photons flux rate at the 26-34 nm spectral band, which is geo-effective in the ionization of the mono-atomic oxygen in the Earth's atmosphere. The results are supported by the comparison of GSFLAI wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 26 publications
(31 reference statements)
5
61
0
Order By: Relevance
“…Since EUV bands are optically thick in the solar atmosphere, flares originating closer to the center of the solar disk are more geo‐effective than those closer to the limb [ Qian et al , ]. Sometimes, after the arrival of a solar flare radiation, associated nearly relativistic electrons can also arrive, typically several minutes after the onset of the EM signature of the solar flare [ Simnett , ; Hernández‐Pajares et al , , Figure 6], which may affect the readings of direct sensors such as the SOHO solar EUV monitor (SEM). But since these electrons enter the Earth's atmosphere through the polar caps, the associated increase in ionization in the atmosphere does not follow the expected flare over ionization dependence of the solar zenith angle, and then it can be filtered out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since EUV bands are optically thick in the solar atmosphere, flares originating closer to the center of the solar disk are more geo‐effective than those closer to the limb [ Qian et al , ]. Sometimes, after the arrival of a solar flare radiation, associated nearly relativistic electrons can also arrive, typically several minutes after the onset of the EM signature of the solar flare [ Simnett , ; Hernández‐Pajares et al , , Figure 6], which may affect the readings of direct sensors such as the SOHO solar EUV monitor (SEM). But since these electrons enter the Earth's atmosphere through the polar caps, the associated increase in ionization in the atmosphere does not follow the expected flare over ionization dependence of the solar zenith angle, and then it can be filtered out.…”
Section: Introductionmentioning
confidence: 99%
“…In the following sections we will show how solar flares can be monitored using GPS data and how the high geo‐effectiveness of solar EUV radiation allows for the determination of its flux rate by measuring the ionospheric response to solar flares. A previous study by Hernández‐Pajares et al [] on this subject mainly focused and demonstrated the approach, for X class flares. Recently, this GNSS‐ionospheric proxy of the solar EUV flux rate has been used to characterize the main statistical properties of solar flares [ Monte‐Moreno and Hernández‐Pajares , ].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the high spatial coverage and good temporal continuity of GPS, some researchers evaluated in detail the global variations of SITEC during solar flares in recent years [e.g., Wan et al ., ; Liu et al ., ; Hernández‐Pajares et al ., ; Xiong et al ., ]. Afraimovich et al .…”
Section: Introductionmentioning
confidence: 99%
“…The system also includes two real-time products relying on solar flare nowcasting, which are based on Global Navigation Satellite Systems (GNSS) for monitoring the daylight ionospheric overionization caused by an increase of electromagnetic radiation associated with solar flares: the so-called GNSS Solar Flare Detector (GSFLAD; Hernández-Pajares et al 2012) and the Sunlit Ionosphere Sudden Total Electron Content Enhancement Detector (SISTED; García-Rigo 2012). These products are not used for solar flare or SEP predictions within SEPsFLAREs but can themselves be useful for real-time monitoring of space launch activities, complementing other flare detection products (e.g.…”
Section: System Overviewmentioning
confidence: 99%